Endoparasites of lizards in caatinga habitats of the semiarid northeast of Brazil - Azevedo Cavalcante, Leonides (2025)
This study characterizes the structure of endoparasite communities associated with lizards from six Caatinga vegetation areas, Brazil and provide a detailed review of the occurrence and geographic distribution of the endoparasite species found. A total of 451 specimens from 16 lizard species from six sample locations within the Caatinga domain were examined. Endoparasites were surveyed in the digestive system, lungs, heart, liver, kidneys, and thoracic cavity. A total of 1648 was collected from 196 hosts, resulting in an overall prevalence of 43.46% and a mean infection intensity of 8.41 (Range: 1-80). The parasitic community was composed of Acanthocephala, Cestoda, Nematoda and Pentastomida. We identified 21 parasite species, which Parapharyngodon alvarengai Freitas, 1957, Physaloptera sp. and Physalopteroides venancioi Lent, Freitas & Proença, 1946 were the most generalists in terms of host species infected, while Centrorhynchus sp., Parapharyngodon largitor Albo & Rodrigues, 1963, Skrjabinellazia galiardi Chabaud, 1973, Spauligodon sp. were the most specialized parasites found. This study brings 19 new host records along with their corresponding geographic areas. The data presented expands our understanding of endoparasites in the most human-populated semi-arid region in the world, advancing the knowledge of the distribution of parasitic species in the Caatinga and reducing the gaps in parasitological information related to lizards from the semiarid region of Northeast Brazil.